" Grenzlandpolitik" und Ostforschung an der Peripherie des Reiches Das ostpreußische Masuren 1919-1945 - Kossert, Andreas 1970- (Vierteljahrshefte für Zeitgeschichte, 2003)
For centuries the Eastern periphery of the Prussian Empire was home to a population composed of several different ethnic groups. One of them, the Mazurians, succeeded in harmoniously integrating German and Polish culture. It was only with the rise of nationalism that both the Prusso-Germans and the Poles began to instrumentalise the Mazurians for their respective political goals. The resulting conflict reached its climax after the First World War, when Poland claimed that Mazuria was "old Polish soil". At the same time, the German home organisation started a vigorous campaign of "Germanization", which was officially termed a preventive measure against the "Polish threat". This campaign was ideologically supported by German scholars, who had devised the scheme within the framework of the so-called "Ostforschung". Along with a strong anti-Polish revisionist policy, Weimar historians established a vocabulary which undoubtedly helped to pave the way for future National Socialist ideas. Contemporary studies on the subject of Mazuria clearly mirror significant changes in the academic community before 1933 as compared to the time after. They also show that some scholars were personally committed to contribute to the final "Germanization" of the Mazurians. (Vierteljahrshefte für Zeitgeschichte / FUB)